Analisis Uji Destructive Dan Non Destructive Terhadap Hasil Sambungan Las V-Tunggal Baja AISI 1045 - Nafrizal . (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Lampung, 2011)
This paper reports the result of study on the strength behaviour of welded joint both destructive and nondestructive testing. The parent metal choosen for the testing was AISI 1045 steel with main parameters of single-V welded form and horizontal welding position. The electrodes used for each parameter were AWS E-7016 LB-52 with diameter/amperes of 2.6 mm/80 Amp, 3.2 mm/110 Amp, and 4.0 mm/130 Amp. The specimens were nondestructively tested using the well-known radiography X-ray according to ASTM-1A for detecting welding flaws and its size. Chemical composition test was performed for the material of parent and welding metal. Tensile testing was performed to destructive based on the ASTM E-8 standard for tensile test. The results show that the tensile strength of the weld joint is reduction by about 28% compared to the parent metal without welding. The reduction in tensile strength is believed to be caused by welding defect, include porosity, inclusion, incomplete penetration, and reduction in carbon content from 0.5% in parent metal to about 0.1% in the welding region. Keywords: smaw, tensile strength, welding defect